The effect of three days of judo training sessions on the inflammatory response and oxidative stress markers - Laskowski, R.; Ziemann, E.; Olek, R. A.; Zembron-Lacny, A. (Journal of Human Kinetics, 2011)
The main purpose of this study was to investigate how extreme physical strain influences cytokine response and oxidative stress markers by examining professional judo athletes during a typical 3-day judo training session (randori combat training). Creatine kinase (CK) activity, a marker of muscle damage, was considerably elevated immediately after randori training. Pro- (IL-1Beta and TNF-Alpha) and anti-inflammatory (IL-6 and IL-10) cytokines were also increased. The strongest effect was seen in IL-1Beta concentration, which correlated with CK activity (r = 0.49, P < 0.05). All the observed cytokines returned to baseline (IL-1Beta) or even dropped below initial levels (TNF-Alpha, IL-6 and IL-10) 12 h after completing the training. Lipid peroxides (LPO), a marker of reactive oxygen species, also decreased below their initial values. LPO levels correlated directly with IL-1Beta, TNF-Alpha, IL-6 and IL-10. This study is the first to evaluate the effect of a 3-day judo training session on muscle damage by evaluating the release of pro- and anti-inflammatory cytokines and markers of oxidative stress. It is also the first to demonstrate significant changes in the blood cytokine profile that correlate with lipid peroxide levels and muscle damage.